Structural types of micro toponyms of Velyki Didushychi of Stryj district of Lvov region (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
The article presents an analysis of structural features of microtoponyms of Velyki Didushychi village of Stryiskyi district Lviv region. The compound two-word constructions include include three derivative models: adjective+noun, numeral+noun, noun+noun. On the premises of the village there are 48 two-member microtoponyms, among which the largest group is presented by onyms attributed by a possessive adjective (25 onyms). The least productive are the microtoponyms distinguished by ordinal numerals containing indication to the ordinal number of a definite denotatum and microtoponyms with the paradigm noun+noun. The group of microtoponyms containing more than two words are represented by six paradigms: numeral+adjective+noun, preposition+adjective+noun,  noun+preposition+noun in the genitive case, preposition+noun+noun, preposition+numeral+noun, noun+appellation (genitive case)+proper name (genitive case). It has been distibguished that a significant part of microtoponyms of Velyki Didushychi village are prepositional word combinations which characterize objects on different features (68 units), the most productive prepositions among them being near, behind, on, at.
Keywords: microtoponyms; two-word combinations; prepositional word combinations; reference names; pattern; attribute; noun; adjective